Serological changes in the course of traditional and biological disease modifying therapy of rheumatoid arthritis. Issue 2 (19th October 2012) - Böhler, Christoph; Radner, Helga; Smolen, Josef S; Aletaha, Daniel
Abstract : Objective: To investigate changes of rheumatoid factor (RF) and antibodies against citrullinated peptides (ACPA) during therapy with disease modifying antirheumatic drugs. Methods: We obtained clinical and serological data of patients from the treatment start and after 6 months of therapy. With non-parametric tests, we analysed changes of ACPA and RF levels between the two visits and the influence of treatment response. Furthermore, we analysed potential influential factors as disease chronicity, different therapeutics and the trend over 18 months. Results: 143 ACPA and RF positive patients were included. The median (25th/75th percentile) relative changes after 6 months were −35.6% (−63.3; −8.3) for RF and −15.2% (−40.0; 10.0) for ACPA (p<0.001 for both). Changes of RF levels were significantly greater than those seen for ACPA (p<0.001). The decrease of ACPA and RF was significantly higher in treatment responders (p=0.034 and p=0.01, respectively). Aside from changes in disease activity, only a short disease duration showed an independent effect on changes of RF levels (p=0.087). Conclusions: ACPA and RF levels decreased significantly after 6 months of therapy. Reductions of both autoantibodies were closely linked to a reduction of disease activity. RF declined faster, to a larger extent and in greater numbers of patients than ACPA.